Development of Visual Motion Perception for Prospective Control: Brain and Behavioral Studies in Infants - Agyei, Seth B.; van der Weel, F. R. (Ruud); van der Meer, Audrey L. H. (Frontiers in Psychology, 2016)
During infancy, smart perceptual mechanisms develop allowing infants to judge time-space motion dynamics more efficiently with age and locomotor experience. This emerging capacity may be vital to enable preparedness for upcoming events and to be able to navigate in a changing environment. Little is known about brain changes that support the development of prospective control and about processes, such as preterm birth, that may compromise it. As a function of perception of visual motion, this paper will describe behavioural and brain studies with young infants investigating the development of visual perception for prospective control. By means of the three visual motion paradigms of occlusion, looming, and optic flow, our research shows the importance of including behavioural data when studying the neural correlates of prospective control.